Elderly Fall Detection for Smart Home Caring Using YOLOv8 - Verma A.; Verma H.; Saket R.K. (My University, 2025)
Climate variability and climate change cause of drought events. Drought is a significant impact of economic, environment and social. The suitable methods in inspecting and monitoring provide useful information that can be used to build up prevention and mitigation planning from drought impacts. The study purposes were to find out the suitable drought index and its trend for the Northern of Thailand. The 10 stations meteorological data during 1951-2020 were used for the drought indices calculation. The indices were Standardized Precipitation Index (SPI), Deciles index and Moisture Available index (MAI) at 1, 3, 6 month timescales and monthly Palmer Drought Severity Index (PDSI). It found that PDSI was the most appropriate index. Consequently, the Mann-Kendal test was used to investigate the trend of PDSI for long-term (40 years) and short-term (20 years) periods. There was no trend of drought intensity for long-term period but found in 4 stations for short-term period. The PDSI can be used for drought monitoring and prediction by using numerical weather prediction products. © (2024) All Rights Reserved.